Reactive leptin resistance and the profile of platelet activation in acute ischaemic stroke patients - Lukasik, Maria; Michalak, Slawomir; Dworacki, Grzegorz; Siewiera, Karolina; Kaczmarek, Mariusz; Watala, Cezary; Kozubski, Wojciech (Thrombosis and Haemostasis, 2012)
SummaryLeptin is an adipokine that in vitro enhances agonist-induced platelet aggregation and adipokine expression. Hyperleptinaemia represents a risk factor for cardiovascular disease. We conducted a prospective evaluation of the potential link between blood platelet activation and plasma leptin levels in post-stroke patients. Using five-colour flow cyto-metry, the platelet surface expression of CD40L, CD62P, the subpopulations of monocyte-platelet aggregates and platelet-derived microparticles (PMPs) as well as the plasma leptin, soluble leptin receptor (sOb-R), leptin/sOb-R ratio, the plasma adiponectin, and leptin/adiponectin ratio were assessed in 98 stroke patients on the first (V0), 10th (V1) and 90th (V2) day after stroke and once in 78 age-, gender- and vascular risk factor-matched disease controls. We demonstrated that at V0 leptin resistance, defined as leptin/sOb-R ratio, was higher than in the controls [1.1 (0.5–1.8 vs. 0.5 (0.2–1.1); p=0.02]. After adjustment according to the factors which influence platelet activation, we confirmed the relationship between percentage of circulating PMPs and plasma leptin level (B=0.18; p=0.02) or the leptin/sOb-R ratio (B=0.23; p=0.02) in normal-weight subjects in the acute phase of stroke. No correlation could be demonstrated between the adipokine parameters and the percentage of monocyte-platelet aggregates or expression of platelet pro-inflammatory glycoproteins. In conclusion, formation of PMPs on the first day following an ischaemic stroke shows a positive correlation with leptin levels and with resistance to leptin. Leptin level does not seem to affect the expression of platelet surface proinflammatory glycoproteins.
Keywords: Leptin; platelet microparticles; P-selectin; CD40L; monocyte-platelet aggregates; ischaemic stroke